1996
DOI: 10.1007/bf02310697
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy of dermatophilosis—A preliminary study

Abstract: In view of the unpredictability of results of antibiotic therapy of bovine dermatophilasis and following the report of successful use of 10% formalin administered intravenously at the dosage of 20ml per lOOkg body weight, a trial was undertaken to evaluate the latter treatment in naturally-occurring dermatophilosis in a group of Friesian crossbred cattle. Group 1 animals were given only 10% formalin. Group 2 received 10% formalin and long-acting oxytetracycline (L/AO) at a dosage of 20mg per kg body weight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Clinical and bacteriological cures were achieved at the 4th week post treatment representing a 100% cure rate in both groups. Previously, Ilemobade (1984), Aning and Koney (1996), Awad et al (2008), Nath et al (2010 and Gebreyohannes and Gebresselassie (2013) reported the efficacy of long acting oxytetracyclines in the treatment of animal dermatophilosis. Also Gbodi and Ndife (1982), Rosyehuk (1989), Yeruham et al (1995), Reed et al (2004 and Aitken (2007) proved the efficacy of penicillin in the treatment of animal dermatophilosis.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical and bacteriological cures were achieved at the 4th week post treatment representing a 100% cure rate in both groups. Previously, Ilemobade (1984), Aning and Koney (1996), Awad et al (2008), Nath et al (2010 and Gebreyohannes and Gebresselassie (2013) reported the efficacy of long acting oxytetracyclines in the treatment of animal dermatophilosis. Also Gbodi and Ndife (1982), Rosyehuk (1989), Yeruham et al (1995), Reed et al (2004 and Aitken (2007) proved the efficacy of penicillin in the treatment of animal dermatophilosis.…”
Section: Discussionmentioning
confidence: 98%
“…However, clinical studies have indicated the efficacy of several antimicrobial treatments. Tetracyclines, long acting oxytetracycline in particular, have been shown to be effective in the treatment of dermatophilosis [ 16 , 17 ]. However, using the microbiological criterium, we demonstrated that six isolates had higher susceptibility results for chlortetracycline and tetracycline, strongly indicating that these isolates had an acquired resistance mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It presents as a chronic or acute exudative dermatitis with scab formation on the skin. The disease had been reported to be more severe in ruminants and is of particular importance in the tropics and sub‐tropics where it can cause substantial economic losses (Zaria ; Aning & Koney ; Ambrose et al . ; Makinde et al .…”
Section: Introductionmentioning
confidence: 99%